Penegakan Pengawasan Ketenagakerjaan terhadap Pelanggaran PKWT di PT. Perikanan Indonesia Dihubungkan dengan Peraturan Menteri Ketenagakerjaan Republik Indonesia Nomor 1 Tahun 2020 - Ujang Charda S; Sri Nurcahyani; Rahmat Saputra (Journal of Innovative and Creativity, 2025)
Violations of labor norms in employment relationships still frequently occur, particularly regarding the application of employment status. Law No. 13 of 2003 on Labor, as amended by Law No. 6 of 2023 on Job Creation, regulates employment relationships based on Indefinite-Term Employment Contracts (PKWTT) and Fixed-Term Employment Contracts (PKWT). However, in practice, violations of PKWT are more commonly found. This study aims to identify the challenges in enforcing labor inspections regarding violations of PKWT at PT. Perikanan Indonesia, referencing Minister of Labor Regulation No. 1 of 2020 amending Minister of Labor Regulation No. 33 of 2016 on Procedures for Labor Inspections. The research method used is descriptive analytical with a normative legal approach. The research was conducted through literature review and field research using data collection techniques such as document analysis and interviews. The data obtained were analyzed using qualitative legal analysis methods. The research findings indicate that, first, labor inspections regarding violations of fixed-term employment contracts at PT. Perikanan Indonesia have been conducted in accordance with the authority and procedures stipulated in the regulations. The process includes receiving reports, conducting field inspections, issuing Special Inspection Notices, summoning officials, and delivering recommendations for administrative sanctions in the form of revoking company licenses. Second, the main obstacle in enforcing supervision is that the Special Inspection Notices issued by supervisors do not have binding legal force and are not enforceable, even though they have been submitted to the court for approval. Additionally, the authority to enforce administrative sanctions lies with the Investment and Integrated One-Stop Service Agency, not with labor inspectors, making it difficult to conduct further oversight and monitor the implementation of sanctions.